2,2-Dimethyl-5-(1-naphthylaminomethylene)-1,3-dioxane-4,6-dione - Zhi Li; Rui Li; Zhen-Yu Ding (Acta Crystallographica Section E, 2009)
The benzyl ring of the title compound, C17H15NO4, is twisted away from the plane defined by five atoms of the dioxane ring by 34.83 (4)°. The dioxane ring exhibits a half-boat conformation, with the C atom between the dioxane O atoms 0.571 (8) Å out of the plane through the remainder of the ring. An intramolecular N—H...O hydrogen bond may contribute to the stabilization of the planar conformation of the molecule. In the crystal, inversion dimers linked by pairs of C—H...O bonds occur.